THU0399 Female sexual dysfunction in patients with idiopathic inflammatory myopathies. (12th June 2018) - Hermankova, B.; Spiritovic, M.; Smucrova, H.; Oreska, S.; Storkanova, H.; Pavelka, K.; Senolt, L.; Mann, H.; Vencovsky, J.; Tomcik, M.
Abstract : Background: Idiopathic inflammatory myopathies (IIM) are characterised by inflammation and atrophy of skeletal muscles, pulmonary and articular involvement, which leads to functional impairment, reduced quality of life including sexual life. Objectives: To assess sexual functions/quality of life and pelvic floor function in female IIM patients compared to age-/sex-matched healthy controls (HC). Methods: In total, 22 women with IIM [mean age: 55.1, disease duration: 7.9 years, dermatomyositis (DM, 8)/polymyositis (PM, 10)/necrotizing myopathy (IMNM, 3)/inclusion body myositis (IBM, 1)], who fulfilled the Bohan/Peter 1975 criteria for DM/PM, and 22 healthy controls (mean age: 55.1 years) without rheumatic diseases filled in 12 well-established and validated questionnaires assessing sexual function/quality of life, pelvic floor function, fatigue, physical activity and depression. Data are presented as mean ±SEM. Results: Compared to HC, patients with IIM had significantly higher prevalence and greater severity of sexual dysfunction (FSFI, BISF-W: in all subscales as well as total scores), dysfunction of pelvic floor (PISQ-12), and worse sexual quality of life (SQoL-F) (table 1). Worse scores in IIM patients were associated with elevated muscle enzyme levels [lactate dehydrogenase: FSFI (r=-0.524, p=0.0123), BISFW (r=-0.528, p=0.0115)], greater fatigue [FIS: FSFI (r=-0.434, p=0.0438), BISF-W (r=-0.488, p=0.0211), SQoL-F (r=-0.488, p=0.0070), PISQ-12 (r=0.643, p=0.0013)], more severe depression [BDI-II: PISQ-12 (r=0.474, p=0, 0258)], deteriorated quality of life [HAQ: PISQ-12 (r=0.476, p=0.0252)], and worse ability to perform physical activities [HAP: FSFI (r=0.437, p=0.0417), BISF-W (r=0.451, p=0.0351), PISQ-12 (r=-0.494, p=0.0195)]. Conclusions: Women with IIM reported significantly impaired sexual function, sexual quality of life and pelvic floor function than age-matched healthy controls. Worse scores in IIM were associated with disease activity, physical activity, fatigue, depression and quality of life. Acknowledgements: Supported by AZV-16–33574A and MHCR 023728. Disclosure of Interest: None declared